2018
DOI: 10.1016/j.jgr.2016.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Gintonin absorption in intestinal model systems

Abstract: BackgroundRecently, we identified a novel ginseng-derived lysophosphatidic acid receptor ligand, called gintonin. We showed that gintonin induces [Ca2+]i transient-mediated morphological changes, proliferation, and migration in cells expressing lysophosphatidic acid receptors and that oral administration of gintonin exhibits anti-Alzheimer disease effects in model mice. However, little is known about the intestinal absorption of gintonin. The aim of this study was to investigate gintonin absorption using two m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…Second, gintonin also restored the hypoxia-induced damages to cell viability by increasing the release of VEGF; however, the gintonin-induced VEGF release and cell proliferation under hypoxia was attenuated by a VEGF antagonist, showing that the regulation of VEGF by gintonin might be crucial for recovering from hypoxic insults. In our previous studies, we also showed that gintonin increases the formation of VEGF in the endothelial cells of human umbilical vein [25]. Thus, combining the results of the present and previous studies, the fact that gintonin regulates the release and expression of VEGF in neural and nonneuronal cells is further substantiated.…”
Section: Discussionsupporting
confidence: 87%
“…Second, gintonin also restored the hypoxia-induced damages to cell viability by increasing the release of VEGF; however, the gintonin-induced VEGF release and cell proliferation under hypoxia was attenuated by a VEGF antagonist, showing that the regulation of VEGF by gintonin might be crucial for recovering from hypoxic insults. In our previous studies, we also showed that gintonin increases the formation of VEGF in the endothelial cells of human umbilical vein [25]. Thus, combining the results of the present and previous studies, the fact that gintonin regulates the release and expression of VEGF in neural and nonneuronal cells is further substantiated.…”
Section: Discussionsupporting
confidence: 87%
“…Orally administered medicines are normally absorbed by the gastrointestinal layer. Lee et al showed that gintonin is significantly absorbed by the intestine [ 14 ].…”
Section: Absorption Of Gintoninmentioning
confidence: 99%
“…The energy-dependent absorption profile of ginsenosides in the mucosa of intestine [ 43 45 ], and the availability of both intact ginsenosides and their metabolites from the intestines are very low [ 39 , 46 , 47 ]. Gintonin can be absorbed into the intestine via transcellular and paracellular diffusion and the active transport process [ 48 ]. In general, the time for ginsenosides to reach maximum concentration (Tmax) in plasma is less than 2 hr, signifying that saponins are quickly absorbed and readily distributed in tissues [ 49 , 50 ].…”
Section: Pharmacokinetics Of Active Ginseng Componentsmentioning
confidence: 99%